A longer isoform of Stim1 is a negative SOCE regulator but increases cAMP‐modulated NFAT signaling. (23rd December 2021) - Knapp, Mona L; Alansary, Dalia; Poth, Vanessa; Förderer, Kathrin; Sommer, Frederik; Zimmer, David; Schwarz, Yvonne; Künzel, Nicolas; Kless, Achim; Machaca, Khaled; Helms, Volkhard; Mühlhaus, Timo; et al.
Abstract: Alternative splicing is a potent modifier of protein function. Stromal interaction molecule 1 (Stim1) is the essential activator of store‐operated Ca 2+ entry (SOCE) triggering activation of transcription factors. Here, we characterize Stim1A, a splice variant with an additional 31 amino acid domain inserted in frame within its cytosolic domain. Prominent expression of exon A is found in astrocytes, heart, kidney, and testes. Full‐length Stim1A functions as a dominant‐negative regulator of SOCE and ICRAC, facilitating sequence‐specific fast calcium‐dependent inactivation and destabilizing gating of Orai channels. Downregulation or absence of native Stim1A results in increased SOCE. Despite reducing SOCE, Stim1A leads to increased NFAT translocation. Differential proteomics revealed an interference of Stim1A with the cAMP‐SOCE crosstalk by altered modulation of phosphodiesterase 8 (PDE8), resulting in reduced cAMP degradation and increased PIP5K activity, facilitating NFAT activation. Our study uncovers a hitherto unknown mechanism regulating NFAT activation and indicates that cell‐type‐specific splicing of Stim1 is a potent means to regulate the NFAT signalosome and cAMP‐SOCE crosstalk. SYNOPSIS: Alternative splicing of the Ca 2+ regulator gene (STIM1) is able to interfere both with ion channel (ORAI) gating and with Ca 2+ ‐cAMP crosstalk to adjust for cell‐type‐specific transcription factor activation. STIM1A is a STIM1 splice variant with an extended C‐terminal domain expressed in distinct cells and tissues. STIM1A destabilizes gating of ORAI channels. Interaction of STIM1 with PDE8 is disabled by splicing‐in of the C‐terminal domain. STIM1A increases local cAMP to stabilize the NFAT signalosome. Abstract : Alternative splicing of the Ca 2+ regulator gene (STIM1) is able to interfere both with ion channel (ORAI) gating and with Ca 2+ ‐cAMP crosstalk to adjust for cell‐type‐specific transcription factor activation.